Will we find Martian lightning via Schumann resonances? - Esman, T. M.; Espley, J. R.; Gruesbeck, J. R.; Verbiscer, A.; Giacalone, J.; Halford, A. J. (Frontiers in Astronomy and Space Sciences, 2023)
Schumann resonances are electromagnetic resonances generally associated with lightning.If they exist on Mars, Schumann resonances are expected to resonate within the ionospheric cavity at a fundamental frequency of 7-14 Hz. We conducted a search for 5 -16 Hz signals below 400 km in magnetic field data from the Mars Global Surveyor (MGS) and Mars Atmosphere and Volatile Evolution (MAVEN) missions. We discuss our null results and the required steps forward to continue and improve this search. Future studies will require higher sensitivity instruments and would benefit from additional missions that reach into the lower ionosphere of Mars.